Answer:
6x² - xy - 15y²
Step-by-step explanation:
To multiply these two binomials together, we can use FOIL. FOIL stands for:
First: Multiply the first terms of the binomials together.
Outer: Multiply the first term of the first binomial by the second term of the second binomial.
Inner: Multiply the second term of the first binomial by the first term of the second binomial.
Last: Multiply the second (last) terms of the two binomials together.
(3x - 5y)(2x + 3y) = (3x)(2x) + (3x)(3y) + (-5y)(2x) + (-5y)(3y)
= 6x² + 9xy - 10xy - 15y²
= 6x² - xy - 15y²
I hope you find my answer helpful.
Look it up find the answer on google
Answer:
16+2x-5adn
Step-by-step explanation:
6+2x-5adn-4+14. solution: is 16=2x-5adn
Multiply 2 by -6.
y=2x-1
y=2(-6)-1
y= -12-1
y= -13
Answer: The answer is your bad, you shouldnt be "answering" questions with " sorry i need points"